Access control in information security: A systematic reviewof current techniques - Pacheco, Jean (2024)
In today’s dynamic cybersecurity scenario, effective managementof access to critical systems and data is essential to safeguardthe integrity and confidentiality of information. This articlepresents a systematic review of the most prominent accesscontrol techniques in the last five years (2019-2023), with theaim of providing an updated view of trends in informationsecurity. The review, based on a meticulous selection of articlesfrom Scopus, SciELO, IEEE and Google Scholar, adheres tothe PRISMA methodology to ensure a rigorous and completesystematic review. Advanced techniques such as CP-ABE,ABAC, RBAC, ACE-BC, ABSE, among others, were identifiedand evaluated, which represent significant advances in accesscontrol and the protection of sensitive information. The resultsobtained highlight the critical importance of these techniquesin information security, providing a clear overview of the mosteffective tools in the protection of digital assets. Ultimately, thisreview not only informs the latest trends but also drives futureresearch in the area of access control and information security.